Ketone Bodies and Acute Energy Compensation in Women Following Exercise - Duquet, Miryam (Université d'Ottawa / University of Ottawa, 2022)
Acute EC (energy compensation) can occur following an exercise session in women. In recent years, the popularity of ketogenic diets or exogenous ketone bodies has drastically increased, namely due to their appetite sensation suppressive effect. The objective of this thesis is to explore the proposed effects of ketogenic diets and exogenous ketone bodies on acute EC in women following a session of exercise. Over a short period, the EC in women following exercise is partially compensated and seems to be the results of many individual factors. LCKD (Low-carbohydrate Ketogenic Diet) results in a decrease in appetite and EI (energy intake) for a short time, but this effect does not appear to be efficient to modulate EI for a duration over 12 months. EKE (Exogenous ketone esters) are a novel product that can allow a rapid increase in blood BHB (β-3-hydroxybutyrate) levels. Their effects on appetite are still elusive, as EKE decrease acute appetite sensations, but this does not translate into a decrease in EI. To date, the impact of EKE on EC in women following exercise remains unknown. Further studies are needed to better understand the regulatory roles of ketone bodies on exercise-induced energy compensation.
Keywords: appetite; women; energy compensation; exogenous ketone esters; low-carbohydrate ketogenic diet